2014
DOI: 10.1111/wrr.12122
|View full text |Cite
|
Sign up to set email alerts
|

A pilot trial using topical regular crystalline insulin vs. aqueous zinc solution for uncomplicated cutaneous wound healing: Impact on quality of life

Abstract: When wounds are treated with regular insulin, they are also being treated with zinc; used in the formula to crystallize insulin molecules. It is not clear if regular insulin-accelerated wound healing is due to insulin, the zinc it contains, or both. Thus, we aimed to compare topical regular crystalline insulin (containing zinc) vs. aqueous zinc chloride solution to controls, on healing of open uncomplicated cutaneous wounds. In this randomized controlled pilot study, 90 nondiabetic patients were randomly assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 17 publications
2
47
0
Order By: Relevance
“…Their results showed that the insulin and zinc solution induced faster wound healing than saline treated groups. However, the insulin treated groups appeared to provide a superior effect compared with the zinc group, but this effect was not significant due to the heterogeneity of the wounds types and sizes (Attia, Belal et al 2014). …”
Section: Insulinmentioning
confidence: 99%
“…Their results showed that the insulin and zinc solution induced faster wound healing than saline treated groups. However, the insulin treated groups appeared to provide a superior effect compared with the zinc group, but this effect was not significant due to the heterogeneity of the wounds types and sizes (Attia, Belal et al 2014). …”
Section: Insulinmentioning
confidence: 99%
“…The possibility that insulin may promote wound healing following simple deep burn skin flap transplantation in humans and its possible mechanism were analyzed in this clinical case-control study. Regular insulin was chosen because of its higher purity, easy absorbability, fast actions, and infimal probability of causing anaphylactic reactions (11). From the research findings it may be concluded that the wound healing rate of the low-dose insulin group significantly improved, the wound healing time shortened, the flap survival rate increased and the wound blood flow volume increased.…”
Section: Discussionmentioning
confidence: 99%
“…The antibody was applied to the ulcers either as a 10 mg/mL solution covered with an adhesive sheet or as a gel formulation (0.45, 1 or 4.5 mg/g) under a hydrofiber dressing adhesive sheet. Although a cocktail containing additional healing agents (Attia et al, 2014;Burek-Kozlowska et al, 1994;Jackson et al, 2012;Kopecki et al, 2013;Pinho et al, 2014;Ruzehaji et al, 2014) may have an improved effect, this initial pioneering study is important in demonstrating the feasibility of the topical route in the clinical setting and again suggests that a high local concentration of anti-TNF favors prompt and definitive healing. Supporting evidence was recently provided by Teich & Klugmann (Teich & Klugmann, 2014), who reported a rapid improvement in refractory pyoderma gangrenosum, a reaction causing local skin ulceration, following the topical application of Infliximab in a sterile hydroxylethyl cellulose gel.…”
Section: Dermal Usementioning
confidence: 97%